Genome-Wide Analysis of the Glucose-6-Phosphate Dehydrogenase Family in Soybean and Functional Identification of GmG6PDH2 Involvement in Salt Stress - Zhao, Ying; Cui, Yifan; Huang, Shiyu; Yu, Jingyao; Wang, Xinyu; Xin, Dawei; Li, Xin; Liu, Yonghui; Dai, Yuxin; Qi, Zhaoming; Chen, Qingshan (Frontiers in Plant Science, 2020)
Glucose-6-phosphate dehydrogenase (G6PDH) is known as a critical enzyme responsible for nicotinamide adenine dinucleotide phosphate (NADPH) generation in the pentose phosphate pathway (PPP), and has an essential function in modulating redox homeostasis and stress responsiveness. In the present work, we characterized the nine members of the G6PDH gene family in soybean. Phylogenic analysis and transit peptide prediction showed that these soybean G6PDHs are divided into plastidic (P) and cytosolic (Cy) isoforms. The subcellular locations of five GmG6PDHs were further verified by confocal microscopy in Arabidopsis mesophyll protoplasts. The respective GmG6PDH genes had distinct expression patterns in various soybean tissues and at different times during seed development. Among them, the Cy-G6PDHs were strongly expressed in roots, developing seeds and nodules, while the transcripts of P-G6PDHs were mainly detected in green tissues. In addition, the activities and transcripts of GmG6PDHs were dramatically stimulated by different stress treatments, including salt, osmotic and alkali. Notably, the expression levels of a cytosolic isoform (GmG6PDH2) were extraordinarily high under salt stress and correlated well with the G6PDH enzyme activities, possibly implying a crucial factor for soybean responses to salinity. Enzymatic assay of recombinant GmG6PDH2 proteins expressed in E.coli showed that the enzyme encoded by GmG6PDH2 had functional NADP+-dependent G6PDH activity. Further analysis indicated overexpression of GmG6PDH2 gene could significantly enhance the resistance of transgenic soybean to salt stress by coordinating with the redox states of ascorbic acid (AsA) and glutathione (GSH) pool to suppress reactive oxygen species (ROS) generation. Together, these results indicate that GmG6PDH2 might be the major isoform for NADPH production in PPP, which is involved in the modulation of cellular AsA-GSH cycle to prevent the oxidative damage induced by high salinity.